2003
DOI: 10.1021/ja021176z
|View full text |Cite
|
Sign up to set email alerts
|

La3+-Catalyzed Methanolysis of Hydroxypropyl-p-nitrophenyl Phosphate as a Model for the RNA Transesterification Reaction

Abstract: The methanolysis of hydroxypropyl-p-nitrophenyl phosphate (HPNPP, 1) promoted by La(OTf)(3) under buffered conditions was studied in methanol as a function of pH at 25 degrees C. (31)P NMR studies at -90 degrees C indicate that there are at least three La/1 complexes formed at pH approximately 5.3 of 1:1, 2:2, and 1:2 stoichiometry. Kinetic studies of the observed pseudo-first-order rate constants for the methanolysis of 1 as a function of [La(3+)] at 4.5 < pH < 10.5 indicate there are two general pH regimes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 53 publications
1
53
1
Order By: Relevance
“…Natural abundance and bridge-labeled isotopic isomers of HpPNP were made using a slight adaptation of a previously published procedure5 which was in turn adapted from the original synthetic procedure 2. The procedure used is illustrated in the following example: 11 mL of propylene oxide (157 mmol) and 360 mg (0.828 mmol) of the di-cyclohexylammonium salt of p -nitrophenyl phosphate ( p -NPP) were stirred vigorously at 30°C in 10 mL of water in a capped round bottom flask.…”
Section: Methodsmentioning
confidence: 99%
“…Natural abundance and bridge-labeled isotopic isomers of HpPNP were made using a slight adaptation of a previously published procedure5 which was in turn adapted from the original synthetic procedure 2. The procedure used is illustrated in the following example: 11 mL of propylene oxide (157 mmol) and 360 mg (0.828 mmol) of the di-cyclohexylammonium salt of p -nitrophenyl phosphate ( p -NPP) were stirred vigorously at 30°C in 10 mL of water in a capped round bottom flask.…”
Section: Methodsmentioning
confidence: 99%
“…OMe for this process is 2.6 × 10 −3 dm 3 mol −1 s −1 at 25 °C [29,30]. A subsequent study of the kinetics of the cyclization of 6a-g promoted by the dinuclear Zn(II) complex 8 revealed that the general mechanism involves saturation binding of the substrate to the complex followed by unimolecular decomposition of a 8:6 complex to give the corresponding phenoxide products and the cyclic ester 7 [31] as in eq.…”
Section: The Cleavage Of a Series Of 2-hydroxypropyl Aryl Phosphates mentioning
confidence: 96%
“…HPNPP was prepared according to a literature procedure [19]. A stock solution (10 mM) of HPNPP in Millipore water was prepared.…”
Section: Kinetic Measurementmentioning
confidence: 99%